Cognitive Phenotypes and the Evolution of Animal Decisions. (November 2016) - Mendelson, Tamra C.; Fitzpatrick, Courtney L.; Hauber, Mark E.; Pence, Charles H.; Rodríguez, Rafael L.; Safran, Rebecca J.; Stern, Caitlin A.; Stevens, Jeffrey R.
Abstract : Despite the clear fitness consequences of animal decisions, the science of animal decision making in evolutionary biology is underdeveloped compared with decision science in human psychology. Specifically, the field lacks a conceptual framework that defines and describes the relevant components of a decision, leading to imprecise language and concepts. The 'judgment and decision-making' (JDM) framework in human psychology is a powerful tool for framing and understanding human decisions, and we apply it here to components of animal decisions, which we refer to as 'cognitive phenotypes'. We distinguish multiple cognitive phenotypes in the context of a JDM framework and highlight empirical approaches to characterize them as evolvable traits. Trends: Animal decisions are the result of multiple interacting cognitive phenotypes. Proximate and ultimate explanations of decisions require the characterization of cognitive phenotypes. We provide an ontology of cognitive phenotypes in a JDM framework. Empirical examples of successfully characterized cognitive phenotypes are highlighted.